REALISASI ELEKTROKARDIOGRAF BERBASIS KOMPUTER PERSONAL UNTUK AKUISISI DATA ISYARAT ELEKTRIS JANTUNG - Agung, IGAP Raka (Majalah Ilmiah Teknologi Elektro, 2005)
Heart is a vital organ in human body that function to pump blood to the body. Pumping activity by heart muscles can be measured using an instrument called electrocardiograph(ECG). Using comercial electronic component can be realized a personal computer based electrocardiograph (PC ECG).This PC ECG consists of electrodes, cables, buffer, Wilson circuit, multiplexer, amplifier, filter, ADC, PPI and PC as main processor. Each components have been realized is tested to find result as its designing. Noise in the ECG signal is filtered using moving average methode. These signals is then represented in the waveform, graph and histogram. ECG components have been made that have shown suitable result as design on its testing. ECG appearance have resembled performance comercial instrument. Moving average filter work properly when delay element is single.